SEORANG PENDERITA DENGAN KARSINOMA SEL SKUAMUS ESOFAGUS - Arsana, I Putu; Wibawa, I Dewa Nyoman (journal of internal medicine, 2010)
Oesophageal carcinoma still rare in Indonesia. Several centers reported low prevalence of oesophageal carcinoma.Three patients found in Palembang in one year, while four patients found in Bandung within ! ve years. Esophageal carcinomawas found in 1.1% of all cancer, and 7% of all digestive organ cancers in United States. Oesophageal carcinoma have mortalityratio of 0.95%. Oesophageal carcinoma more frequent in men with a ratio of 3:1. Diagnosis by anamnesis, physical examination,routine blood tests, barium esophagogram, esofago-gastroduodenoscopy, chest and abdominal CT-scan or MRI, bronchoscopy,endoscopic ultrasound, and also with laparoscopy. A 55-years old Balinese woman came with complaints of dif! culty inswallowing and diagnosed as squamous cell middle third oesophageal carcinoma stage III. Anamnesis, barium esofagogram,gastroduodenum endoscopy (OGD), and histopathological biopsy con! rmed the diagnosis of this patient. This patient givenchemotherapy with combination of 5-